Anti-inflammatory Activity of Kheaw-Hom Remedy in Lipopolysaccharide-stimulated Macrophage Cells and Carrageenan-induced Paw Edema in Rats - Sukkasem, Kanmanee; Itharat, Arunporn; Thisayakorn, Krittiya; Panthong, Sumalee; Makchuchit, Sunita; Inprasit, Janjira; Prommee, Nuntika; Khoenok, Wicheian; Sriyam, Kanjana; Pahusee, Darunee (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Kheaw-Hom (KH) remedy has been widely used to treat inflammation and fever in children with measles and chickenpox. However, its anti-inflammatory activity, both in vitro and in vivo, has not been scientifically tested. Objectives: To evaluate the in vitro and in vivo anti-inflammatory activities of KH remedy. Methods: The in vitro anti-inflammatory activities of the aqueous extract (KHA) and ethanolic extract (KHE) were investigated using lipopolysaccharide (LPS)-stimulated nitric oxide (NO), prostaglandin E2 (PGE2 ), and tumor necrosis factor-alpha (TNF-α) in macrophage RAW 264.7 cells. The in vivo anti-inflammatory activity of KHE and KH powder (KHP) was determined using carrageenan-induced paw edema in rats and the PGE2 production in tissue samples was examined using ELISA kit. Results: KHE exhibited anti-inflammatory activities through the suppression of PGE2 , NO, and TNF-α production with IC50 values of 19.69 ± 2.09, 39.93 ± 3.28, and 85.07 ± 2.61 μg/ mL, respectively, while KHA did not. Interestingly, KHP orally administered at the dose of 100 mg/kg significantly reduced rat paw edema at 1, 2, and 3 hours (37.25%, 25.00%, and 27.09%, respectively) while KHE at the dose of 100 mg/kg noticeably reduced at 2 and 3 hours (21.67% and 19.49%) after carrageenan injection. KHP at the dose of 100 mg/kg showed maximum inhibition of PGE2 production with the PGE2 levels of 15.46 ± 1.33 ng/mL. Conclusions: The findings from in vivo study strongly parallel the results of the in vitro study and support the traditional use of KH as a potent anti-inflammatory and antipyretic remedy.